Komunikasi Mitigasi Bencana Pada Peserta Didik Sekolah Dasar - Siregar, Mariana Rista Ananda; Sariswara, Valianty; Nuraisyiah, Siti Fathonah (JURNAL KOMUNIKATIO, 2025)
This study aims to analyze the disaster mitigation communication steps implemented by the Citeko Meteorological Station of BMKG through the "BMKG Goes To School" program targeted at elementary school students in disaster-prone areas. The research employed a qualitative case study approach, with data collected through in-depth interviews, participant observations, and document analysis, and processed using the atlas.ti version 9 software. The findings reveal that the implementation of disaster communication follows five key strategic steps: (1) Situational awareness is achieved by utilizing local disaster risk maps and weather forecasts; (2) Customer focus is applied by tailoring messages to children's cognitive levels using simple language, visuals, animations, and thematic songs; (3) Leadership commitment is shown through the active involvement of the station head in both planning and implementation; (4) Inclusion of communication in planning and operations is reflected in the assignment of a trained team and the execution of earthquake simulation drills; and (5) Media partnership has limited impact due to the primary audience’s low access to digital media. The study recommends incorporating training for teachers and establishing a structured evaluation framework to enhance the program's communication effectiveness.